Pengukuran Beban Kerja Mental Menggunakan Metode RSME di Damkar Kab. Bone Bolango - Mamonto, Nisfa; Mardjun, Muh Khairullah; Hunta, Moh Fahrizan; Pomalingo, Muhariyanto; Mohamad, Silvana; Fais, Moh Ainul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study was conducted to determine the level of mental workload experienced by firefighters in Bone Bolango Regency, Gorontalo. The method used was the Rating Scale Mental Effort (RSME), with the research subjects consisting of three work shifts, each containing nine officers. The measurements focused on the level of mental effort required when performing tasks such as standing by, extinguishing fires, rescuing people, and other support tasks that require full attention. The results showed that each shift had a different mental workload score, influenced by incidents, pressure to act quickly, and unpredictable waiting conditions. Overall, the RSME scores indicate that most officers fall into the moderate to high mental load category, especially in activities that require high concentration and quick decisions. These findings show that firefighting work not only relies on physical strength but also requires strong mental preparedness to ensure personal and public safety.